The motivations that define eating patterns in some Mediterranean countries. Issue 6 (11th November 2019) - Guiné, Raquel; Ferrão, Ana Cristina; Ferreira, Manuela; Correia, Paula; Cardoso, Ana Paula; Duarte, João; Rumbak, Ivana; Shehata, Abdel-Moneim; Vittadini, Elena; Papageorgiou, Maria
Abstract : Purpose: This study to investigate several issues related to food choice and consumption patterns in different countries, including health-related factors; economic and availability aspects; emotional determinants; social, cultural and religious influences; marketing and advertising campaigns; and finally environmental concerns. Design/methodology/approach: The present study was based on a questionnaire that was exclusively prepared for the project, and which was applied to collect data in different countries, in particular Croatia, Egypt, Italy, Greece and Portugal, which are typically associated with the Mediterranean diet (MD). Findings: The results obtained allowed, in general, to conclude that in all five countries the motivations related to health as well as environment and politics were the more relevant to determine people's eating habits (scores varying from 0.3 to 0.7). Women were more influenced by eating motivations than men, and people with moderate exercise were more susceptible to health and environmental motivations and less to emotional, social or marketing motivations ( p < 0.001 in all cases). It was also observed that people who adopted a special diet were more prone to eating motivations and that the emotional motivations were more pronounced in people with eating disorders ( p < 0.001). Finally, people without chronic diseases or allergies were even more influenced by health motivations than those who actually suffered from these health problems ( p < 0.001 in both cases). Originality/value: This work is important because of the multinational coverage, thus allowing to evaluate the most relevant factors that influenced the food choices of the populations around the Mediterranean Sea, sharing the common link to the MD. The study allowed concluding that, in general, the food choices were primarily determined by health factors and also by concerns related to the environment and sustainability as well as by political influences.